Analisis Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern pada Perusahaan Real Estate Dan Property Yang Terdaftar di BEI Tahun 2017-2020 - Firda Nindy Pangestu; Shita Tiara (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the factors that influence going concern audit opinions on real estate and property companies listed on the Indonesia Stock Exchange in 2017-2020. This study uses an associative quantitative descriptive approach. The type of data in this study is secondary data, in the form of sample company financial statements. The population in this study are real estate and property companies listed on the Indonesia Stock Exchange as many as 53 companies. The sampling method used is purposive sampling method, in order to obtain 25 sample companies with 4 years of research. The data analysis techniques used are factor analysis, descriptive statistical analysis, multicollinearity test, logistic regression analysis, analysis model testing and hypothesis testing. The results of this study partially show that the variables of firm size, KAP reputation, and liquidity have a significant effect on going concern audit opinion. While the variables of audit quality, profitability, solvency, cash flow, and previous year's audit opinion have no significant effect on going concern audit opinion. Then simultaneously the variables of firm size, KAP reputation, audit quality, profitability, liquidity, solvency, cash flow and previous year's audit opinion have a positive and significant effect on going concern audit opinion.